Integrated Application of Transcriptomics and Metabolomics Reveals the Energy Allocation-Mediated Mechanisms of Growth-Defense Trade-Offs in Crassostrea gigas and Crassostrea angulata - Wang, Chaogang; Li, Ao; Wang, Wei; Cong, Rihao; Wang, Luping; Zhang, Guofan; Li, Li (Frontiers in Marine Science, 2021)
Understanding the genetic basis of trait variations and their coordination between relative species or populations distributing in different environmental conditions is important in evolutionary biology. In marine ectotherms, growth-defense trade-offs are a common ecological and evolutionary phenomenon. However, the biochemical and molecular mechanisms that govern these trade-offs in marine ectotherms in the evolutionary perspective remain poorly investigated. Oysters are among the most important species in global aquaculture. Crassostrea gigas (C. gigas) and Crassostrea angulata (C. angulata) are two allopatric congeneric dominant oyster species that inhabit the northern and southern intertidal areas of China. Wild C. gigas and C. angulata were spawned, and their F1 progeny were cultured in the same sites to reduce the environmental effects. Untargeted metabolomics and transcriptomics, together with phenotypic parameters including morphological traits (growth performance), nutritional content (glycogen, crude fat, and fatty acid content), physiology (normalized oxygen consumption rate and total antioxidant capacity) were applied to assess metabolic and transcript divergences between C. gigas and C. angulata. Integrated analyses of metabolites and transcriptomes showed that C. gigas allocated more energy to storage and defense by suppressing glycolysis, fatty acid oxidation and by upregulating fatty acid synthesis, antioxidant gene expression, and related metabolites. The metabolic and transcript results were further confirmed by the phenotypic data that C. gigas has higher glycogen and crude fat content and fatty acid unsaturation and stronger antioxidant capacity than C. angulata. In contrast, C. angulata exhibited better growth performance and a higher oxygen consumption rate. These findings suggest that C. angulata allocates more energy to growth, which is embodied in its stronger aerobic capacity and higher levels of protein synthesis genes, metabolites, and growth-related biomarkers. This study will help to enlighten the evolutionary patterns and genetic basis of growth-defense trade-offs in marine ectotherms and the biochemical and molecular mechanisms underlying energy allocation. Also, the key genes and metabolites of glycogen and fatty acids pathway identified in this study will be applied for meat quality improvement in the oyster industry.